PIAS family in cancer: from basic mechanisms to clinical applications - Li, Xiaomeng; Rasul, Azhar; Sharif, Farzana; Hassan, Mudassir (Frontiers in Oncology, 2024)
Protein inhibitors of activated STATs (PIAS) are proteins for cytokine signaling that activate activator mediated gene transcription. These proteins as versatile cellular regulators have been described as regulators of about 60 proteins. Dysregulation of PIAS is associated with inappropriate gene expression that promotes oncogenic signaling in multiple cancers. Multiple lines of evidences have revealed that PIAS family members show modulated expressions in cancer cells. Most frequently reported PIAS family member in cancer development are PIAS1 and PIAS3. SUMOylation as post-translational modifier regulates several cellular machineries.PIAS proteins as SUMO E3 ligase factor promotes SUMOylation of transcription factors tangled cancer cells for survival, proliferation, as well as differentiation. Attenuated PIAS-mediated SUMOylation mechanism is involved in tumorigenesis. This review article provides PIAS/SUMO role in modulation of transcriptional factor control, brief update on their antagonistic function in different cancer types with particular focus on PIAS proteins as a bonafide therapeutic target to inhibit STAT pathway in cancers and summarizes natural activators that may have the ability to cure cancer.